Emotion in the 2019 Teenagers Historical Novels Competition - Roslan, Nur Maisarah; Subramaniam, Vijayaletchumy; Redzuan Abdullah, Muhammad Alif (Human Resource Management Academic Research Society, 2023)
Mobility program has been carried out in universities from all over the world as it is the most popular program among the university students. This is due to the fact that the mobility program will ensure a starter link and communication among universities. The objective of this study was to identify the communication strategies used by the inbound mobility students from the non-speaking English countries in Universiti Putra Malaysia. The samples of the study consisted of 20 respondents and they were 7 male and 13 female mobility students from Asian and European universities who were attending the mobility program at Universiti Putra Malaysia. The methods involved in this study was observation sessions. Observation sessions were video-taped. The study only focuses on the communication strategies used among inbound mobility students and the understanding, opinion and idea of the mobility program to the inbound mobility students at Universiti Putra Malaysia. As for the procedure of the study, the subjects were informed about the observation sessions which were video-taped. An area of topics was given to the subjects to be discussed. This study used Communication Strategies Theory by Dornyei & Scott (1997). The results of the study showed that there was a large amount of communication strategies used among inbound mobility students at UPM during their conversation discussions. Although the mobility students were able to speak in the English language, it can be said that the language spoken had errors in sending the message across to the listener. It is also believed that the errors made were all common among the inbound students and not much help was given to them to overcome the issues. Therefore, the need to use communication strategies were important to enhance learning. It is hoped that further studies will focus on the long-term inbound mobility program.